Проблеми оцінки комунікаційної діяльності в роздрібній торгівлі - Майстро, Руслана Григорівна; Васильєва, Катерина Володимирівна (НТУ "ХПІ", 2015)
У статті розглядаються теоретичні підходи до оцінки комунікаційної діяльності торгівельного підприємства, досліджуються існуючі методи аналізу, їх переваги та недоліки в роботі роздрібної торгівлі та доводиться роль та значимість цього процесу для розвитку українських підприємств в сучасних умовах ведення бізнесу. Сьогодення підприємств вимагає широкого використання різноманітних комунікаційних інструментів, тому уміння формувати комунікаційну політику компанії, а особливо оцінювати та аналізувати ефективність комунікаційної діяльності, є вкрай важливими.

The article analyzes theoretical approaches to the evaluation of communication activities of trade enterprise, studied the existing methods of analysis, their advantages and disadvantages in the retail trade and proved the role and importance for the development of Ukrainian enterprises in today's business environment. Real of the business requires extensive use of various communication tools, that is why the ability to shape the company's communication policy, and especially to evaluate and analyze the effectiveness of communication activities, is extremely important. Also in the article the essence of the management of the communication activities of trade enterprise, identified the main problems and the main directions of their solution.
Problems evaluation the effectiveness of communication activities in retail trade
Keywords: комунікації маркетингові; ефективність економічна; ефективність психологічна; marketing communications; economic efficiency; psychological efficiency